Judicial Approach for Promotion of Good Governance of Natural Resources in Sri Lanka - Sarveswaran, A. (My University, 2010)
Unsustainable exploitation, mismanagement, improper alienation and corruption relating to natural resources generate various types of conflicts mostly intra state conflicts or sometimes lead to relapse into conflicts in post-conflict states. Hence, good governance of natural resources becomes a prerequisite to sustainable development and sustainable peace in a country. In Sri Lanka, the legislature has enacted many laws relating to natural resources to empower the authorities to protect, exploit, manage and alienate natural resources. When the authorities arrogate and abuse the powers and engage in corrupt practices, it becomes important to the judiciary to intervene to promote good governance of the resources. The Court of Appeal has intervened to issue writs when the established procedures including public hearing have not been followed in making decisions affecting natural resources. The Supreme Court has invoked mainly the public trust doctrine and the concepts of sustainable development and inter-generational equity under its fundamental rights jurisdiction to strike down the deals that were entered into through abuse of powers, corruptive practices and circumvention of relevant legal provisions. It has interpreted Article 12(1) of the Constitution to give effect to the provisions of the ordinary legislation of the country. These approaches of the judiciary make the authorities to apply the provisions of the ordinary legislation relating to natural resources for the intended purposes of the legislation without abusing their powers or engaging in corrupt practices.
Keywords: sustainable development; Good Governance; Natural Resources; public trust doctrine